2016
DOI: 10.7554/elife.18449
|View full text |Cite
|
Sign up to set email alerts
|

Antiparallel protocadherin homodimers use distinct affinity- and specificity-mediating regions in cadherin repeats 1-4

Abstract: Protocadherins (Pcdhs) are cell adhesion and signaling proteins used by neurons to develop and maintain neuronal networks, relying on trans homophilic interactions between their extracellular cadherin (EC) repeat domains. We present the structure of the antiparallel EC1-4 homodimer of human PcdhγB3, a member of the γ subfamily of clustered Pcdhs. Structure and sequence comparisons of α, β, and γ clustered Pcdh isoforms illustrate that subfamilies encode specificity in distinct ways through diversification of l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 55 publications
2
41
1
Order By: Relevance
“…The γB2 EC1–5 and γB7 EC1–4 trans dimer structures show the same overall arrangement as the previously published γB3 EC1–4   trans dimer structure (Nicoludis et al, 2016). However, closer analysis revealed that the γB3 EC1–4 structure is an outlier among the γB structures, both in terms of its overall structure (Figure 1—source data 3–7), and in the interactions at the recognition interface (Figure 1—figure supplement 3).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The γB2 EC1–5 and γB7 EC1–4 trans dimer structures show the same overall arrangement as the previously published γB3 EC1–4   trans dimer structure (Nicoludis et al, 2016). However, closer analysis revealed that the γB3 EC1–4 structure is an outlier among the γB structures, both in terms of its overall structure (Figure 1—source data 3–7), and in the interactions at the recognition interface (Figure 1—figure supplement 3).…”
Section: Resultssupporting
confidence: 84%
“…Excluding the structurally diverse γA-Pcdhs and the partially occluded γB3 dimer (Nicoludis et al, 2016), the EC1–4 dimers of isoforms from the same subfamily have similar overall structures (RMSDs ~1.5–3.4 Å; Figure 1—source data 3). This similarity is even more apparent when the two mutually exclusive interaction regions (EC1:EC4 and EC2–3:EC2–3) are compared separately revealing RMSDs of <2 Å (Figure 1—source data 4–5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using sequence coevolution analysis and comparison to γ-Pcdh structures, it was suggested that non-clustered Pcdhs likely interact via antiparallel EC1-4 contacts, in a manner similar to the clustered Pcdhs [62]. Recently, Cooper et al [72] reported structural data for EC1-4 of zebrafish Pcdh19, a δ2-Pcdh family member, which indicate a similar architecture to that of clustered Pcdhs.…”
Section: The Non-clustered Protocadherinsmentioning
confidence: 99%